Do CEOs' demographic characteristics affect firms' risk-taking? Evidence from Jordan - Ruba Bsoul; Rawan Atwa; Mahmoud Odat; Lara Haddad; Mamoun Shakhatreh (Cogent Business & Management, 2022)
The upper echelons theory suggests that directors' characteristics, values, and professional experience have an impact on their perceptions, and thus their own decisions. Building on this theory, this study aims to examine the impact of CEOs' demographic characteristics on firms' risk-taking. The analysis is based on a sample of 82 manufacturing and service companies listed on the Amman Stock Exchange for the period 2015-2019. The CEO characteristics examined include gender, age, qualification, experience, ownership, duality, and tenure. Though, we use the standard deviation of the firm's return on assets ratio as a measure for risk-taking. The results indicate that there is a significant negative relationship between CEO qualification, experience, ownership, and Jordanian firms' risk-taking. While there is a significant positive relationship between CEO tenure and Jordanian firms' risk-taking. Importantly, CEO gender, age, and duality are unrelated to firms' risk-taking in Jordan. This study contributes significantly to the existing, but limited, literature that examines the relationship between the CEOs' demographic characteristics and firms' risk-taking. It is worth noting that, this The study is the first in Jordan to investigate the impact of the CEOs' demographic characteristics on firms' risk-taking and document the above-mentioned relationships. The findings of the study could bring the attention of the standard setters and regulators to the importance of CEOs' attributes on controlling the mechanisms of the firms' risk-taking, and thus enable Jordanian companies to take the right decisions in relation to CEO appointments, as such decisions would certainly affect the company's performance and sustainability in the long-run.
Keywords: M12; M41; 650; CEO characteristics; Duality; Performance; Risk-taking; Tenure